Hubungan Response Time Seksio Sesarea Emergensi Kategori 1 dengan Luaran Perinatal di RSUP Dr.Sardjito - Gunawan, Tri; Attamimi, Ahsanudin; Pradjatmo, Heru (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: Caesarean section is often applied as a preventif efoort against the continued effects of perinatal asphyxia. The cesarean section (SC) in pregnant woman can be performed in a planned manner with various indications or performed by emergency (emergency) on maternal or fetal indications and or both.Objective: To study the association of response time in category I emergency caesarean section with perinatal outcomes in Dr. Sardjito hospital and the average response time of category 1 emergency cesarean section in Dr. Sardjito hospital.Method: This study uses retrospective cohort. Category 1 CS with an indication of fetal accordance with the inclusion criteria was recorded from 1st January 2012 until 31th July 2016, then we find the response time mean as the cut off point of this study to compare with their perinatal outcomes.Result and Discussion: There were 155 cases out of 386 of emergency CS category 1 met the inclusion criteria during the period 1st January 2012 to 31th July 2016. From the data obtained, the average response time of category 1 emergency CS was 115±52 minutes (35 - 360 minutes). We found no significant differences in perinatal outcomes in the group’s response time ≥115 minutes with a value of p>0.05 on the Apgar score, CPAP, infant mortality, ventilator, NICU care, MAS and HIE than those category 1 emergency CS with a response time <115 minutes. From multivariate analysis, general anaesthesia was statistically significant against perinatal outcomes Apgar score <7 at 5 minutes with (p=0.044). Prematurity in the multivariate analysis was statistically significant against perinatal outcomes Apgar score ≤3 at 1 minute with (p=0.040), Apgar score <7 at 5 minutes with (p=0.025) and the use of CPAP with (p=0.009).Conclusions: Response time category 1 emergency cesarean section in this study did not affect perinatal outcomes. General anesthesia effect on perinatal outcomes Apgar score <7 at 5 minutes, whereas the prematurity effect on perinatal outcomes Apgar score ≤3 at 1 minute, Apgar score <7 at 5 minutes and the use of CPAP.Keywords: category 1 emergency caesarean section, response time, fetal distress